Crime and criminal justice in Europe and North America: 1995 - 1997; report on the Sixth United Nations Survey on Crime Trends and Criminal Justice Systems - Aromaa, Kauko (Publication series, 2003)
The purpose of the report is to describe public safety in the European and North American region as a whole, and in the individual countries within the region. The report is based on an analysis of national responses to the Sixth United Nations Survey of Crime Trends and Operations of Criminal Justice Systems. It covers the years 1995 through 1997. The Sixth United Nations Survey data have been supplemented by other information, including in particular the results of the International Crime Victim Survey.